2021
DOI: 10.1038/s41598-021-01930-y
|View full text |Cite
|
Sign up to set email alerts
|

Correlates of neutralizing/SARS-CoV-2-S1-binding antibody response with adverse effects and immune kinetics in BNT162b2-vaccinated individuals

Abstract: While mRNA vaccines against SARS-CoV-2 are exceedingly effective in preventing symptomatic infection, their immune response features remain to be clarified. In the present prospective study, 225 healthy individuals in Japan, who received two BNT162b2 doses, were enrolled. Correlates of BNT162b2-elicited SARS-CoV-2-neutralizing activity (50% neutralization titer: NT50; assessed using infectious virions) with various determinants were examined and the potency of sera against variants of concerns was determined. … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
60
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 64 publications
(69 citation statements)
references
References 37 publications
7
60
2
Order By: Relevance
“…Not only high Ab responses against SARS-CoV-2 spike protein but also systemic adverse effects induced by the BNT162b2 vaccine were reported to be more common among participants with preexisting immunity due to COVID-19 infection [ 10 ], suggesting that some systemic adverse effects are induced as a more vigorous response to the SARS-CoV-2 spike protein itself produced by the BNT162b2 vaccine. Previous publications reported that adverse effects induced by the BNT162b2 vaccine had no correlation or only low correlation with Ab titers detected immediately after vaccination [ 5 , 6 , 7 , 8 ]. However, to evaluate the long-term effects of vaccination, research should consider Ab titers several months after vaccination and not only the peak level of Ab titers.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Not only high Ab responses against SARS-CoV-2 spike protein but also systemic adverse effects induced by the BNT162b2 vaccine were reported to be more common among participants with preexisting immunity due to COVID-19 infection [ 10 ], suggesting that some systemic adverse effects are induced as a more vigorous response to the SARS-CoV-2 spike protein itself produced by the BNT162b2 vaccine. Previous publications reported that adverse effects induced by the BNT162b2 vaccine had no correlation or only low correlation with Ab titers detected immediately after vaccination [ 5 , 6 , 7 , 8 ]. However, to evaluate the long-term effects of vaccination, research should consider Ab titers several months after vaccination and not only the peak level of Ab titers.…”
Section: Discussionmentioning
confidence: 99%
“…If the maximum vaccine efficacy, including antibody (Ab) responses, is guaranteed, most people will accept a certain severity of vaccination-related adverse effects [ 2 ]. Although several reports concluded that there is no correlation or only low correlation between adverse effects and the Ab titers detected immediately after vaccination [ 5 , 6 , 7 , 8 ], a correlation is expected between adverse effects and the Ab titers detected several months after vaccination [ 9 ]. Antibody titers alone do not correlate perfectly with protection because the benefits of mRNA vaccines include not only B-cell/humoral responses but also T-cell/cell-mediated immunity.…”
Section: Introductionmentioning
confidence: 99%
“…While molecular proof of incident infections and the risk of developing severe forms of COVID-19 determine the efficacy of vaccines, serum levels of spike-specific IgG mirror the immune response [ 5 ]. Furthermore, short-term adverse events are common following each dose of the BNT162b2 vaccine, as evident from the reports on self-reporting apps [ 6 ] with a proposed impact on the IgG response [ 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…Some reports suggest that the effectiveness of COVID-19 vaccines may be reduced in patients on anti-CD20 mAbs treatment due to diminished humoral immune responsiveness [ 11 , 12 ]. However, this patient's serum neutralizing antibodies remained remarkably high for at least one month after administration of casirivimab/imdevimab, considering the results of a study of the neutralizing antibody titer after COVID-19 mRNA vaccination (BNT162b2) in healthy individuals [ 13 ]. Although it is unclear how long neutralizing antibodies persist, monoclonal antibody therapy with casirivimab/imdevimab may be useful for COVID-19 prophylaxis in patients with humoral immunodeficiency, in whom vaccine efficacy is low.…”
Section: Discussionmentioning
confidence: 99%